EU Enlargement and Agro-Food Export Performance on EU Market Segments - Štefan Bojnec; Imre Fertő (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
This paper examines the impact of EU enlargement on agro-food export performance across 12 new EU member states and 5 newly independent states in the EU markets covering the period 1999-2007. The performance is examined by duration of export and hazard model. We find larger duration for the agro-food exports from the new EU member states. The results confirm gains from the eastward EU enlargement and governance on export increases and longer duration for exporting higher value-added specialized consumer-ready food and more competitive niche agro-food products.
Keywords: F14; F15; Q17; P27; 330; EU enlargement; governance; agro-food export duration; hazard model; niche products; EU-Mitgliedschaft; Wirkungsanalyse; Export; Agrarprodukt; EU-Mitgliedschaft; EU-Staaten